Effects of dopants with various valences on densification behavior and phase composition of a ZrO2–SiO2 nanocrystalline glass-ceramic. Issue 7 (1st April 2022) - Wang, Bohan; Xu, Guofu; Huang, Jiwu; Engqvist, Håkan; Xia, Wei; Fu, Le
Abstract: Effects of dopants with different valences on the densification behavior and phase composition of a ZrO2 –SiO2 nanocrystalline glass-ceramic (NCGC) during pressureless sintering were investigated in this study. The raw powder of Ca 2+, La 3+, Ce 4+ and Ta 5+ ions doped ZrO2 –SiO2 (referred to as Ca-ZS, La-ZS, Ce-ZS, Ta-ZS, respectively) and pure ZrO2 –SiO2 (PZS) sample were synthesized by sol-gel method, followed by pressureless sintering. Compared with the PZS sample, doping of Ca 2+ and La 3+ ions significantly promoted the densification of the NCGCs. The "densification promotion" effect was attributed to the formation of oxygen vacancies and the decrease of SiO2 viscosity due to doping of aliovalent cations. The dopants with various valences showed significant effects on the phase compositions of the NCGCs during sintering. Doping of Ca 2+ ion accelerated the reaction kinetics between ZrO2 nanocrystallites and amorphous SiO2 to yield ZrSiO4 . The La 3+ ion acted as destabilizer of t-ZrO2, which resulted in a rapid tetragonal (t) to monoclinic (m) ZrO2 phase transformation during sintering, while in the Ta 5+ and Ce 4+ ions doped sample, the phase transformation occurred gradually. All the doping ions increased the lattice parameters and the volume of t-ZrO2 unit cell, while the effects of the doping ions on the lattice parameters of m-ZrO2 unit cell were more complex.